Morning blood pressure surge and dipping profile in non-hypertensive obese subjects. - Hasan, Hayder S.; Almadfai, Zaid; Abdulkareem, Faris (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Obesity is an evolving major health problem in both developed and developing countries. Non-hypertensive obese may have an elevated Morning Blood pressure surge (MBPS), which is associated with increased risk for cardiac events (CE) independently of office and ambulatory blood pressure (BP). Non-hypertensive obese also may have a blunted nocturnal decrease in BP during the night, while healthy normotensive non-obese individuals have a 10%–20% nocturnal decrease in blood pressure (BP) during the night or dipping. Thus, 24-hour ambulatory blood pressure monitor (ABPM) is the gold standard to evaluate MBPS and dipping profile in non-hypertensive obese individuals. Objectives: to measure and evaluate morning blood pressure surge and dipping profile for normotensive obese subjects by using 24-hour Ambulatory blood pressure monitor (ABPM). Methods: A total of 86 asymptomatic obese individuals (54 males, 32 females) were recruited from Obesity Unit in Alkindy College of Medicine/ University of Baghdad. Ambulatory blood pressure monitoring was done in addition to 42 healthy non-obese subjects of either sex served as controls. Fasting blood glucose level was considered for all study subjects in addition to anthropometric measurements. Results: Obese subjects had a significantly higher morning blood pressure surge (MBPS), BMI is positively correlated with MBPS with significance (P=0.0001) with Pearson’s correlation coefficients (r= 0.92). Obese subjects had a significantly higher mean 24-hour, daytime and night systolic/diastolic blood pressure with P value less than 0.0001. The dipping profile of obese subjects revealed a significantly less dipping percent as compared with normal weight control subjects in both systolic and diastolic BP with p = 0.02 and 0.04 for systolic and diastolic blood pressures respectively. Conclusion: BMI is positively correlated with MBPS. In regard to dipping profile, obese subjects had decreased or blunted nocturnal fall in blood pressure. In addition, obese subjects had increased ambulatory blood pressures (systolic, diastolic, daytime and nighttime pressures), emphasizing the strong association between obesity and pathogenesis of hypertension.